2021
DOI: 10.1139/cjpp-2020-0539
|View full text |Cite
|
Sign up to set email alerts
|

MiR-145-5p modulates lipid metabolism and M2 macrophage polarization by targeting PAK7 and regulating β-catenin signaling in hyperlipidemia

Abstract: The present study aims to explore the role of microRNA 145-5p (miR-145-5p) in hyperlipidemia. Using bioinformatics tools and a wide range of function and mechanism assays, we attempted to understand the specific function and potential mechanism of miR-145-5p in hyperlipidemia. A cholesterol-enriched diet induced an increase of serum cholesterol and triacylglycerol but a decrease of serum high-density lipoprotein. MiR-145-5p level was decreased in hyperlipidemia rat models. MiR-145-5p regulated lipid metabolism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 43 publications
1
4
0
Order By: Relevance
“…This is also consistent with results reported on miR-145 targeted using adenoviral vectors and nanomaterials . This may be explained by the regulation of smooth muscle cells’ excessive migration and proliferation, which is the primary cause of plaque formation. , Additionally, the regulation of macrophage proliferation and apoptosis to mitigate inflammatory responses may contribute to a similar effect. , Therefore, treatment with CMBs/agomir-145 + UTMD reduces necrotic cores and plaque size, thereby limiting AS. This finding is corroborated by similar results reported in a previous study on plaque treatment with adenovirus-mediated transfection of miR-145 …”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…This is also consistent with results reported on miR-145 targeted using adenoviral vectors and nanomaterials . This may be explained by the regulation of smooth muscle cells’ excessive migration and proliferation, which is the primary cause of plaque formation. , Additionally, the regulation of macrophage proliferation and apoptosis to mitigate inflammatory responses may contribute to a similar effect. , Therefore, treatment with CMBs/agomir-145 + UTMD reduces necrotic cores and plaque size, thereby limiting AS. This finding is corroborated by similar results reported in a previous study on plaque treatment with adenovirus-mediated transfection of miR-145 …”
Section: Resultssupporting
confidence: 88%
“…15,43 Additionally, the regulation of macrophage proliferation and apoptosis to mitigate inflammatory responses may contribute to a similar effect. 12,44 Therefore, treatment with CMBs/agomir-145 + UTMD reduces necrotic cores and plaque size, thereby limiting AS. This finding is corroborated by similar results reported in a previous study on plaque treatment with adenovirus-mediated transfection of miR-145.…”
Section: 5mentioning
confidence: 99%
“…Wang et al found that miR-145a-5p regulated microglial polarization and the production of inflammatory cytokines, in which the NF-κB pathway might be involved (17). Chen et al reported that miR-145a-5p modulated the polarization of M2 macrophage by targeting PAK7 and regulating β-catenin signaling in hyperlipidemia (53). Moreover, miR-145a-5p regulates the differentiation of myoblasts, adipocytes, and T cells (15,16,54).…”
Section: Discussionmentioning
confidence: 99%
“…Among the enriched miRNAs in MBVs, three were selected according to the sequencing results. All of these miRNAs, miR-125b-5p [93,94], miR-143-3p [95,96], and miR-145-5p [97][98][99], has been reported to contribute to pro-regenerative macrophage phenotype polarization. miRNA inhibition resulted in gene expression patterns opposite those of macrophages treated with MBVs.…”
Section: Residual Cellular Contentsmentioning
confidence: 99%